Introducere în studiul stratificării şi mobilităţii sociale: teorii, măsuri şi modele de analiză. Editura Tritonic, București, 2022. Cătălin Augustin Stoica - Horia Mihai (Sociologie Românească, 2023)
Cătălin Augustin Stoica's volume Introduction to the Study of Social Stratification and Mobility: theories, measures and models of analysis can be considered a starting point in developing a theoretical understanding of the concepts mentioned in the title. Although the book is mainly addressed to students in the area of social sciences, we can say that the language is widely accessible to the general public. It should be appreciated that the reader does not need a theoretical background before reading the book, as each concept is defined and analysed in such a manner, that makes the transition from common knowledge to scientific knowledge. Stratification and social mobility could not be dealt with separately, and in order to make intelligible how these concepts are intertwined in the dynamics of social life, the author presents them in a theoretically evolutionary scale. The explanation of the concepts is carried out starting from classics such as Marx and updated to the contemporary era with the help of authors that include Erik Olin Wright. From the conceptual trunk outlined by the theories of the aforementioned authors, sprout the branches of sub-chapters such as 'Power and Privilege' or 'Theories of the Elites', whose purpose is to broaden the reader's understanding of the subject. Through his book, Cătălin Augustin Stoica succeeds in offering a new approach to concepts studied for many decades in the field of sociology.